Costs and Benefits of Labour Mobility between the EU and the Eastern Partnership Countries Country Study: Italy - Sabrina Marchetti; Daniela Piazzalunga; Alessandra Venturini (Institute for the Study of Labor (IZA), 2013)
Migrants from the Eastern Partnership Countries: Moldova, Ukraine, Belarus, Georgia, Armenia, Azerbaijan has increased in the last ten years. Two different patterns are detected among the most important groups: Ukrainian and Moldovan. The first is mainly composed by women with a temporary migration plan while the second was initially composed by women but rapidly the family reunification was obtained and the migration plan became more permanent. By using the Italian Labour Force survey we analyse the employment situation, the over education of the migrants and their assimilation.
Keywords: J15; J26; J61; J62; 330; migration; labour market